Study of bioheat transfer and cardiac thermal pulse of aneurysm in the abdominal aortic using computational fluid dynamic and fluid structure interaction - Looi, Jun Cong (Nanyang Technological University, 2022)
In this study, the heat transfer and flow physics of Abdominal Aortic Aneurysm (AAA) were discussed and associated with cardiac cycle to illustrate the cardiac thermal pulse (CTP) of AAA. A CTP and IRT evaluation-based on AAA and abdomen skin surface detection method was proposed respectively. The identification of AAA for each scenario was done by evaluating the CTP of abdominal aorta wall. Under regular body temperature, AAA of FSI Analysis did not have a CTP that responded to systole phase which shown in CFD rigid-body analysis. In contrast, the healthy abdominal aorta in CFD rigid-body analysis had a CTP which responded to the entire cardiac cycle, including diastolic phase. As the body experiences fever or stage-2 hypothermia, result from CFD rigid-body analysis indicates that the AAA wall would achieve thermal equilibrium, with blood temperature at a quasi-linear relationship. Yet, at the healthy abdominal aorta, there is CTP detected. Besides, from CFD rigid-body and FSI Analysis, the bioheat transfer effect resulted in a circular thermal elevation on the temperature profile of midriff skin surface patient, at both regular body temperature and supine position, under normal clinical temperature. These findings then correlated the relationship between natural convective heat transfer coefficient with AAA and provided reference for potential clinical diagnostic using infrared thermography (IRT).